(untitled) (Iter, 2022)
In the Greek myth. beauty is regarded as a pleasant gift to divine and human eyes. We should not forget that three goddesses. who are w ornen at last. disputed an apple with the inscription “tt) xocXXÍott| " and they broke out a war. We should also think about the numerous epithets given to gods and moríais with kalli- as first component. •Yoír. if we circumscribe our view to a human and Jema le sphere. the basic question of this research is to solve whether a splendid body results in a reward or a punishment. Among others. attractive characteristics are grace. proportion. freshness. slender. harmony. elegance. all of them accompanied by refmement in gestare and manners. by prudence and melody ¡n the word. good taste in hairdressing. the clothes and the accessories plus uncountable persuasive resources related to the figure and the bearing. The female possessors can be aware of such power and take advantage of it or ignore their own charm and cause more troubles to other people - and to themselves-, The re are different grades of perception of the authority they exert. some times involuntarily and dijferent levels of vanity Such is the case of the boastful Cassiepeia. Andrómeda’ s mother. who knew she was pretty’ indeed and openly competes against the Nereids. Slaves are not an exception: the post Homeric tradition imagined that the captive Briséis was tall. brunette and of radiant eyesight.